2013
DOI: 10.1159/000353414
|View full text |Cite
|
Sign up to set email alerts
|

Age Is Predictive of Immediate Postoperative Urinary Continence after Radical Retropubic Prostatectomy

Abstract: Introduction: Immediate continence is a goal to take into consideration for better patient satisfaction after radical prostatectomy. Factors predicting urinary continence at catheter removal were investigated. Materials and Methods: We evaluated preoperative, operative, clinical, hormonal and pathological variables in a homogeneous series of radical retropubic prostatectomies (RRPs) following the principles of urinary sphincter restoration technique. Results: The study included 201 patients who underwent RRP. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…On the other hand, other studies showed that aging was not associated with delayed continence recovery. 23 In our study, the majority of patient were young, with a mean age of 60 years, and narrowly distributed with an interquartile range of 56-66 years. Therefore, age was not found to be an independent predictor.…”
Section: Rajih Et Al Impact Of Perioperative Factors On Continence Recovery After Rarpmentioning
confidence: 57%
“…On the other hand, other studies showed that aging was not associated with delayed continence recovery. 23 In our study, the majority of patient were young, with a mean age of 60 years, and narrowly distributed with an interquartile range of 56-66 years. Therefore, age was not found to be an independent predictor.…”
Section: Rajih Et Al Impact Of Perioperative Factors On Continence Recovery After Rarpmentioning
confidence: 57%
“…In addition, patients with NB tend to be younger, thereby increasing the likelihood of multiple revisions over the life of the AUS. At the same time, AUS is reported to have good and immediate continence rates in younger PPI patients [7] .…”
Section: Background and Objectivesmentioning
confidence: 94%
“…Higher PSA levels, a higher age and a longer hospitalization period were seen in the RS group and may be related to the unfavourable outcome regarding early continence. This is confirmed in the publication of Campodonico et al 29 Recovery of urinary incontinence should be considered as a process that extends well beyond the hospital stay. While there is little data on early incontinence, the literature allows a clearer assessment of the urinary continence situation of patients in the course of time after RP: the majority of patients are continent three months after surgery.…”
Section: Discussionmentioning
confidence: 70%